Reestruturação agroindustrial e mudanças institucionais na rede láctea paulista. - Cunha, Juliano Cavalheiro da (2005)
In a very complex sector like the milk it is important to discuss the Govern action. This issue has been discussed very hard in all international meetings about trading. In the Brazilian case its possible to visualize two different periods of Government action, the regulation and the self-regulation. So, the processes between these periods has caused different kind of impacts to the actors. Among all the problems created are the exclusion of milk producers, workers and cooperatives. The main issue of this work are the changes happened in the beginning of ninety years, when the Government stopped regulating the milk sector. Another objective is to describe and analyze the formation of the milk policy network in the São Paulo state considering the institutional environment and the governance structure. The object of analyze is the milk policy network, the unit of analyze is the negotiation among the actors and the variable of analyzes are the power resources (constitutional, policy, financial, organizational, technological and juridical).